The Influence of The Growth of Micro, Small, and Medium Enterprises (MSMEs) on Labor Absorption in Central Mamuju District, Indonesia - Syukron Madfuz, Lalu; Tahir, Muh; Halim , Abdul (Golden Ratio of Social Science and Education, 2025)
This quantitative research design aims to determine the growth of Micro, Small, and Medium Enterprises (MSMEs) on labor absorption by taking the research location in Central Mamuju Regency. This research aims to discover more about the growth of MSMEs and their influence on the number of workers who can be absorbed. This research uses a simple linear regression analysis method and a data collection method through documentation. From the t-test results, the calculated t value for the growth variable for micro, small, and medium enterprises (MSMEs) is 6.598, greater than the t-table value of 2.570 with a significant value of 0.001, which is smaller than 0.05. So the first hypothesis is that the growth of micro, small, and medium enterprises (MSMEs) significantly affects labor absorption in Central Mamuju Regency. Meanwhile, the results of the correlation coefficient analysis obtained a correlation coefficient (r) of 0.947 which is included in the powerful correlation category so that the second hypothesis is that the growth of micro, small and medium enterprises (MSMEs) has a robust correlation or relationship with labor absorption in Central Mamuju Regency, accepted.